Spatio Temporal Analysis of Land Use Change for Supporting Landslide Exposure Assessment - Anung . Kurniawan; B.G.C.M (Bart) Krol (Faculty of Geography, Universitas Gadjah Mada, 2014)
Located in landslide prone areas, Cipanas and Pacet sub-districts are placed in areas where land uses are very dynamic. Land use change analysis is needed in these sub-districts for assessing its pattern and the driving factors that caused the change. Moreover, the results from the analysis can be used as input for land use change modeling to predict land use in the future for supporting landslide exposure assessment. ἀe objective of this research is to assess spatio temporal dynamic of landslide exposure by integrating land use change modeling using CLUE-S and landslide exposure assessment. ἀe obtained Kappa value was classiḀed as high agreement. Future land use prediction was conducted by considering three scenarios, baseline scenario (no restriction), scenario 1 (restriction in conservation area), and scenario 3 (restriction in conservation area and landslide prone area). Result of future land use prediction year 2031 in baseline scenario dominated by settlement and infrastructure expansion and forest conversion into another land use. However, implementation of scenario 1 and 2 in the model, were successfully restricts forest conversion and development of settle-ment and infrastructure in landslide prone area. Landslide exposure assessment was conducted by combining weighted asset map and landslide susceptibility map. ἀere were two type of asset considered in this research, social and physical asset. Population density was applied as a factor for social asset, while land use was applied as a factor for physical asset. Weight of assets and their factors was determined based on experts opinion by using Analytic Hierarchy Process (AHP) approach. ἀe result landslide exposure assessment shows that high and medium landslide exposure area follow pat-tern of settlement and infrastructure land use. Future landslide exposure assessment by considering baseline scenario resulted in the increasing of high landslide exposure area in year 2031. On the other hand, by applying restriction in scenario 1 and 2, high landslide exposure can be reduced.